Police Performance Rankings Depend on the Functional Form of the Index: A Comment on Bearfield, Maranto, and Wolf. (4th March 2022) - Reed, David S.
Abstract : Bearfield, Maranto, and Wolf advise policy-makers to measure policing outcomes using a metric that includes rates of homicide, police-related civilian deaths (PRCD), and poverty. They present such an index, which they call the Police Performance Index (PPI). But alternative functional forms that are equally plausible can lead to different rankings of police departments, and therefore different policy conclusions.